Analysis of the Critical Discourse of Richard Eliezer's Confession After the Verdict in the Rosi Program on Kompas TV - Ariyanti Rahayu; Auzar Auzar; Elmustian Elmustian (Yayasan Adra Karima Hubbi, 2024)
Background. Richard Eliezer's confession after the verdict in the Rosi program on Kompas TV attracted public and media attention. This confession contains complex dimensions in terms of legal, social, and psychological aspects that deserve further analysis. The discourse that occurs in this program reflects the dynamics of power and ideology that influence public perception. Purpose. This research aims to analyze the critical discourse of Richard Eliezer's confession after the verdict in the Rosi program on Kompas TV. This analysis will explore how the language and narratives used by Richard Eliezer and the program presenters shape public perception of his case and identify the ideology and power operating behind the discourse. Method. This type of research is descriptive qualitative research. The method of analysis in this research is description and interpretation. The data of this research is taken from the discourse of the news video of Richard Eliezer's expression after the verdict of the murder of Brigadier Yoshua. Results. The results showed that Richard Eliezer's confession was structured with language that sought to construct his image as a victim and seek public sympathy. The program presenter played an important role in reinforcing this narrative through empathetic and supportive questions. The ideologies identified in this discourse include attempts to redefine justice and challenge existing power structures. Conclusion. That the discourse in the Rosi program related to Richard Eliezer's confession after the verdict shows efforts to reconstruct self-image through the strategic use of language and narrative. The discourse not only reflects the power and ideology operating but also directs public opinion towards a particular interpretation of justice. This analysis provides a deeper understanding of how the media can influence perceptions and shape social reality.